2017
DOI: 10.1111/jpim.12435
|View full text |Cite
|
Sign up to set email alerts
|

Foreign and Domestic Collaboration, Product Innovation Novelty, and Firm Growth

Abstract: Although prior research underscores the benefits of external collaboration for a firm's innovative output, little research has examined the role that collaboration plays across the different stages of the innovation process. Drawing from organizational learning theory, this article examines (1) how collaboration with domestic partners assists in the formation of collaborations with foreign partners, (2) how knowledge from these collaborations is associated with product innovation at different levels of novelty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 113 publications
(301 reference statements)
4
107
0
8
Order By: Relevance
“…Ou seja, pode-se afirmar que a existência de um motivo hard, ampliam a probabilidade que a empresa estabeleça um vínculo com a universidade e com instituições públicas de C&T, corroborando com a H1. Este resultado vai de encontro com os estudos de Belderbos et al (2004), Mention (2011), Un e Asakawa (2015), Wirsich et al (2016), Hsieh (2017).…”
Section: Discussão Dos Resultadosunclassified
See 2 more Smart Citations
“…Ou seja, pode-se afirmar que a existência de um motivo hard, ampliam a probabilidade que a empresa estabeleça um vínculo com a universidade e com instituições públicas de C&T, corroborando com a H1. Este resultado vai de encontro com os estudos de Belderbos et al (2004), Mention (2011), Un e Asakawa (2015), Wirsich et al (2016), Hsieh (2017).…”
Section: Discussão Dos Resultadosunclassified
“…Apontar as características-chave no nível da firma é importante no reconhecimento das características que conduzem à procura estas fontes externas de informações. As variáveis selecionadas e muito da discussão aqui apresentada foram baseadas em Laursen e Salter (2004), Theter e Tajar (2008), Hsieh et al (2017) e Bittencourt et al (2018).…”
Section: Características Das Firmas E Uso De Fontes Externas De Inforunclassified
See 1 more Smart Citation
“…Grounding on knowledge-based view and organizational learning theory, previous studies pointed out that geographical diversity provides geographically dispersed knowledge that is lacking in the home state and improves and improving flexibility, responsiveness, and adaptability to foreign markets [46][47][48][49]. Notwithstanding the above benefits, geographical diversity also entails unique challenges from the perspective of transaction cost theory.…”
Section: Alliance Network Geographical Diversity and Innovation Ambidmentioning
confidence: 99%
“…Although some studies empirically have found that geographical diversity leads to high innovation performance [30,49], most of them did not address the issue of the novelty of innovation or distinguish exploratory innovation and exploitative innovation. According to Sarpong and Teirlinck's [42] findings, geographical diversity may not enhance the balance between both exploitative and exploratory innovation.…”
Section: Alliance Network Geographical Diversity and Innovation Ambidmentioning
confidence: 99%